2017
DOI: 10.3390/bios7010011
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Methods for Skeletal Muscle Glycogen Analysis in Athletes—The Need for Novel Non-Invasive Techniques

Abstract: Muscle glycogen levels have a profound impact on an athlete’s sporting performance, thus measurement is vital. Carbohydrate manipulation is a fundamental component in an athlete’s lifestyle and is a critical part of elite performance, since it can provide necessary training adaptations. This paper provides a critical review of the current invasive and non-invasive methods for measuring skeletal muscle glycogen levels. These include the gold standard muscle biopsy, histochemical analysis, magnetic resonance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 71 publications
0
25
0
2
Order By: Relevance
“…This appearance cannot be solely explained by excessive adipose infiltration, since in extreme adipose muscle infiltration, it has been reported that the echogenicity actually decreases . On the contrary, studies have shown that glycogen‐depleted muscles also appear hyperechoic, suggesting a US relationship between increased muscle echogenicity and decreased intramuscular glycogen …”
mentioning
confidence: 99%
“…This appearance cannot be solely explained by excessive adipose infiltration, since in extreme adipose muscle infiltration, it has been reported that the echogenicity actually decreases . On the contrary, studies have shown that glycogen‐depleted muscles also appear hyperechoic, suggesting a US relationship between increased muscle echogenicity and decreased intramuscular glycogen …”
mentioning
confidence: 99%
“…Due to the importance of skeletal muscle glycogen in sports performance, there is a need for monitoring skeletal muscle glycogen in a non-invasive manner [8], as well as for an analysis of the main components involved in glycogen depletion during a match, including frequency, duration, intensity and nutrition, which could contribute to the creation of individualized protocols for carbohydrate administration to soccer players. However, the measurement of skeletal muscle glycogen through a quick and non-invasive tool has remained elusive for many years, being only possible through invasive and non-practical muscle biopsies or expensive and impractical magnetic resonance techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, muscle biopsies are needed to assess muscle glycogen levels [ 1 ]. Biopsies are invasive, painful, and not feasible to use on athletes when they are preparing for a season [ 2 ]. However, a noninvasive approach to quantify glycogen content in the muscles exists via high-frequency ultrasound technology.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ultrasound technology has been found to correlate well with histochemical analyses of rectus femoris (RF) muscle biopsies [ 3 ]. Therefore, ultrasound is a potentially useful tool to incorporate in athlete monitoring protocols to measure glycogen content of the muscle [ 2 ] as an indicator of lower substrate availability, recovery, and dietary habits.…”
Section: Introductionmentioning
confidence: 99%